2019
DOI: 10.1038/s41421-018-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Indispensable role of the Ubiquitin-fold modifier 1-specific E3 ligase in maintaining intestinal homeostasis and controlling gut inflammation

Abstract: Intestinal exocrine secretory cells, including Paneth and goblet cells, have a pivotal role in intestinal barrier function and mucosal immunity. Dysfunction of these cells may lead to the pathogenesis of human diseases such as inflammatory bowel disease (IBD). Therefore, identification and elucidation of key molecular mechanisms that regulate the development and function of these exocrine cells would be crucial for understanding of disease pathogenesis and discovery of new therapeutic targets. The Ufm1 conjuga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 65 publications
1
61
0
Order By: Relevance
“…Linking the fidelity of the UFM1 system via CCND1 to proliferation allows cells to halt the cell cycle if UFMylation, and thus the coordination of translation and secretory protein biosynthesis, is perturbed. Such a role can also explain that tissues specialized in secretion such as the liver, intestine and pancreas are especially sensitive to perturbations in UFM1 system (Cai et al, 2019;Lemaire et al, 2011;Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Linking the fidelity of the UFM1 system via CCND1 to proliferation allows cells to halt the cell cycle if UFMylation, and thus the coordination of translation and secretory protein biosynthesis, is perturbed. Such a role can also explain that tissues specialized in secretion such as the liver, intestine and pancreas are especially sensitive to perturbations in UFM1 system (Cai et al, 2019;Lemaire et al, 2011;Yang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…UFMylation remains crucial in the adult organism as acute ablation of UFL1 or DDRGK1 in mice cause severe anemia and tissue-specific targeting of UFL1 in the heart and gut lead to cardiomyopathy and impaired intestinal homeostasis, respectively (Cai et al, 2019;Li et al, 2018). Beyond model organisms, mutations in UFM1 enzymes are associated with multiple human pathologies including early-onset encephalopathy and defective brain development (Arnadottir et al, 2017;Colin et al, 2016;Duan et al, 2016;Mignon-Ravix et al, 2018;Muona et al, 2016;Nahorski et al, 2018), diabetes (Lu et al, 2008), ischemic heart injury (Azfer et al, 2006), skeletal dysplasia (Watson et al, 2015), atherosclerosis (Pang et al, 2015), Parkinson's disease (Nalls et al, 2014), and cancer (Maran et al, 2013;Yoo et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In parallel, UFM1 has been shown essential for embryonic development, and the prevention of this modification in mice causes severe anemia that leads to the death of the embryo [ 72 ]. More recently, it was shown that UFM1 is also required for the proper development of other tissues, including intestine, heart, and brain [ 30 , 39 , 73 , 74 , 75 , 76 ]. Therefore, over the last few years, the motivation to understand the molecular mechanism of this modification, and in particular the role it plays in these key developmental processes, has significantly increased.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Recently, the ubiquitin-fold modifier 1 (UFM1) conjugation system was characterized as a posttranslational modifier [1][2][3][4]. Ubiquitin-like modifier 1 ligating enzyme 1 (UFL1) is an important E3-ligating enzyme of the UFM1 conjugation system, which is expressed in multiple tissues including heart, liver, intestinal, and pancreatic tissues [5][6][7][8][9]. Further, it is well known that UFL1 is an indispensable component of this system given its involvement in various cellular processes, such as apoptosis [9,10].…”
Section: Introductionmentioning
confidence: 99%